Development and validation of models for analysing the effects of sea-level rise: application in southern Brazil - Lima, Lucas Terres de (2022)
Nowadays, the effects of sea-level rise can be observed in several countries of the world. The continuous rise of the mean sea-level in this century, reported by altimetry sensors and tide gauge data, and the constant increase of gas emissions, which implies the increase of global warming, will lead to global warming and more threatened areas in the future. In Brazil, the main cities are located on the coast site, which means studies that apply mapping and new projections are crucial to identify hazardous areas and prevent the worst scenario in the future. The present work consists in carrying out an analysis of the impact of sea-level rise for the end of this century in Rio Grande do Sul Coastal Plain (Southern Brazil), using three different Geographic Information Systems tools (GIS) created for this study. The tools are a product of an extensive study about sea-level models and coastal barriers that include a topographic and bathymetric survey with Unmanned Aerial Vehicle (UAV), a systematic literature review and the digitization of cross-sections of the stratigraphic coastal barriers of Rio Grande do Sul. The study highlights the scientific production of the region, having collected all the stratigraphic surveys carried out until 2021 and discussed the rise in sea-level related to the formation of coastal barriers. The first tool, named End Point Rate for QGIS (EPR4Q), performs trend analysis of the shoreline, and was validated using the well-known Digital Software Analysis System (DSAS) and Analysing Moving Boundaries Using R (AMBUR) software. The obtained results disclosed a high statistical correlation coefficient of 0.98 and 1.00 on linear, extensive and non-extensive shorelines, respectively. The second tool, called Uncertainty Bathtub Model (uBTM), calculates the probability of sea- level flooding by uncertainties in the projections and showed high correlation values of 0.75 to 1.00 with similar tools (Terrset Sea-level Impact, and Bathub Model). The third tool, Bruun Rule for GEE model (BRGM), applies the Bruun Rule in the GIS environment. Its validation showed a value of 0.97 of statistical correlation. The EPR4Q, uBTM and BRGM tools are open to the scientific community for improvement and to adapt the code for in-house applications and scientific research. The results using EPR4Q in the coastal plain Rio Grande do Sul showed that about 28.60% of the coastline may retreat in 2100, being more severe in the southern areas. In addition, the uBTM pointed to that 38.11 Km² to 44.57 Km² of urban area may be lost due to sea-level flood in 2100. The BRGM model showed a shoreline retreat ranging from -298.45 m to -1.7 Km that reflects the morphodynamical differences between coastal sectors. The results underscore the importance of being warned about the impacts of sea-level rise in Rio Grande do Sul Coastal Plain to provide more evidence for politics and coastal managers so they can act in advance. Therefore, the study carried out confirmed the hypothesis that it is possible to perform initial assessments of sea-level rise with the three tools created, since the study drives similar results (i.e. identification of erosive hotspots) as previously reported from other authors.